¿Cómo transformar un elipsoide en un esferoide? Técnica quirúrgica para la corrección de la sinostosis sagital basada en un modelo geométrico - Morsucci, E.; Houssay, A.; Beninca, J.; Ferraro, Florencia; Ibáñez, M. (Revista Argentina de Neurocirugía, 2021)
INTRODUCTION: Sagittal synostosis is the most common craniosynostosis. There is still debate about which is the most appropriate surgical method for its treatment. This work presents a surgical technique based on a geometric model that answers the question: How to transform an ellipsoid body into a spheroid one? MATERIALS AND METHODS: A surgical technique is described as a method that allows modeling the skull of an infant with dolichocephalic conformation. A geometric model is developed, showing step by step how an ellipsoid figure is modified, improving its width / length ratio. Later, this model in "the map" is transferred to a 3-D model, being able to verify the change of shape. Finally, we present 8 cases of operated patients, showing that the theoretical model correlates with the "in vivo" model. RESULTS: 8 patients with this type of craniosynostosis, 6 boys and 2 girls, were operated on. The ages were from 2 to 7 months. An improvement in the cephalic index (CI) was verified in all of them, measured in the immediate postoperative period. The average CI prior to surgery was 0.67 SD = 0.021 and, for the same population in the postoperative period, it was 0.77 SD = 0.035. Student’s t test for paired samples was 7.84, which gives a null hypothesis P <0.01%. The increase in the index is correlated with age at the time of surgery, (R = 0.76) with a negative coefficient (b = -0.02), which indicates that the best results are observed in younger patients. DISCUSSION: Since the first surgery to correct sagittal synostosis, performed in 1890, different techniques have been proposed. On the one hand the less invasive endoscopic surgery should be supplemented with the use of cranial orthosis (helmet) for several months. On the other hand, there are more invasive surgeries such as total reconstruction of the cranial vault, which would be indicated in older patients. The surgical technique developed here offers an intermediate alternative, which does not require postoperative orthosis, expander devices or prosthetic material. Due to the low incidence of the disease and the few cases operated so far, it remains to be determined up to what age this technique is efficient. CONCLUSION: The present surgical technique, based on a geometric model, offers immediate correction of the cephalic index, demonstrated by quantitative measurements, statistical analysis, images and photographs. Due the few treated cases so far, it remains to be determined up to what age this techniques is efficient.